The Impact of Cooperative Learning Approach on Enhancing EFL Learners Speaking Fluency Skills Case Study 1st Year EFL’s University Students - SOUFFI,Aicha; Gasmi,mustapha (Faculty of Letters and Foreign Languages Department of English, 2025)
This research aims to discuss the importance, and the impact of cooperative learning approach on enhancing EFL learners speaking fluency skills, also to explore the students, and teachers' attitudes and perspectives, towards the (CLA) approach, at Ammar Thledji English language department. The main issue to discuss in this work is how (CLA) approach can facilitate speaking interaction and communication, and what techniques should teachers implement in their classes, to motivate students do more efforts while working in pairs, or smal groups. The traditional methods may not be helpful to develop student's speaking fluency skills whereas (CLA) approach can create a dynamic atmosphere, where students can collaboratively work, think and share their thoughts, ideas easily. Two questionnaires were administrated to 25, 1st year EFL students and 3 EFL teachers.Descriptive, and analytical study has been conducted in the current research. The analysis, and the findings, showed that both, students, and teachers, are aware of the need of the (CLA) approach, and its impact in enhancing, and facilitating learning process.